Effect of allyl-isothiocyanate on survival and antimicrobial peptide expression following oral bacterial infections in Drosophila melanogaster - Zimmermann, Christian; Dähn, Sonja; Wagner, Anika E. (Frontiers in Immunology, 2024)
Since infections with antibiotic resistant bacteria cause increasing problems worldwide, the identification of alternative therapies is of great importance. Plant-derived bioactives, including allylisothiocyanate (AITC), have received attention for their anti-microbial properties. The present study therefore investigates the impact of AITC on survival and anti-microbial peptide (AMP) levels in Drosophila melanogaster challenged with the fly pathogenic bacteria Pectobacterium carotovorum subsp. carotovorum and Leuconosoc pseudomesenteroides. AITC, a sulfur-containing compound derived from glucosinolates, exhibits anti-microbial properties and has been suggested to modulate AMP expression. By using D. melanogaster, we demonstrate that AITC treatment resulted in a concentration-dependent decrease of survival rates among female flies, particularly in the presence of the Gram-negative bacterium Pectobacterium carotovorum subsp. carotovorum while AITC did not affect survival in male flies. Despite the ability of isothiocyanates to induce AMP expression in cell culture, we did not detect significant changes in AMP mRNA levels in infected flies exposed to AITC. Our findings suggest sex-specific differences in response to AITC treatment and bacterial infections, underlining the complexity of host-pathogen interactions and potential limitations of AITC as a preventive or therapeutic compound at least in D. melanogaster models of bacterial infections.